Gastric outlet obstruction due to gastric duplication cysts with heterotopic pancreatic tissue treated by marsupialization - Nicholas J. Skertich; Mary Beth Madonna; Ami N. Shah (Elsevier, 2019)
Gastric duplication cysts are rare congenital anomalies often treated with complete surgical excision, but this is not always possible. In such cases, resection and reconstruction have been advocated, but this may lead to significant morbidity. We present a unique case of a 3-year old girl who presented with complete gastric outlet obstruction due to multiple gastric duplication cysts with heterotopic pancreatic tissue treated with marsupialization and endoscopic surveillance as an alternative to gastric resection and reconstruction. This approach avoids morbidities from a more extensive procedure and in this case, alleviated the obstruction, averted sequelae secondary to heterotopic pancreatic tissue, and provides surveillance in the rare case of malignant degeneration. The child tolerated the procedure well and has been symptom free for the past year. Keywords: Gastrointestinal duplications, Gastric duplication cyst, Gastric outlet obstruction